Pontin, a new mutant p53-binding protein, promotes gain-of-function of mutant p53 - Zhao, Y (Cell Death Differ, 2015)
Tumor-suppressor p53 is frequently mutated in human cancers. Many tumor-associated mutant p53 (mutp53) proteins gain new functions in promoting tumorigenesis, defined as gain-of-function (GOF). The mechanisms for mutp53 GOF are not well understood. Here, we report Pontin, a highly conserved AAA+ ATPase important for various cellular functions, as a new mutp53-binding protein. This Pontin–mutp53 interaction promotes mutp53 GOF in invasion, migration and anchorage-independent growth of tumor cells. The ATPase domain of Pontin is crucial for its promoting effect on mutp53 GOF; blocking the ATPase activity of Pontin by a Pontin-specific ATPase inhibitor or an ATPase-deficient dominant-negative Pontin expression vector greatly diminished mutp53 GOF. Pontin promotes mutp53 GOF through regulation of mutp53 transcriptional activity; knockdown of Pontin abolished the transcriptional regulation of mutp53 toward a group of genes. Furthermore, overexpression of Pontin in tumors is associated with the poor survival in cancer patients, especially those containing mutp53. Our results highlight an important role and mechanism for Pontin, a new mutp53 partner, in promoting mutp53 GOF in tumorigenesis.